Estudo do status taxonômico de uma população de Bothrops gr atrox (Serpentes: Viperidae: Crotalinae) de um brejo de altitude no Nordeste do Brasil - Matias, Cicera Silvilene Leite (2021)
An integrative taxonomy, which combines various analyses of information and characters, can serve as an excellent ally for systematic and taxonomic studies. Knowledge about biodiversity is inherently variable, as new species emerge through taxonomic revisions or new descriptions, while others face extinction, often before they are even recognized by science, particularly in the case of cryptic species. Brazil exhibits an immense richness of reptile species and subspecies, ranking among the highest globally. The country harbors a diversity of 856 species, along with an additional 33 subspecies, currently positioned behind only Australia, with 1,132 species, and Mexico, with 980 species. The genus Bothrops is a clade comprising at least 51 venomous snake species, of which 34 are found in Brazil. Due to the extensive diversity, the relative rarity of certain species, and the phylogenetic divisions within the genus, some species of Bothrops may be considered candidates for critical species status. In this manner, we aim to investigate the taxonomic status of a relictual population of Bothrops gr. atrox recorded in an upland Brejo within the Ibiapaba Plateau, in the state of Ceará. To achieve this goal, we used morphological and molecular data, specifically the 12S gene, and performed molecular phylogenetic analyses, as well as a multivariate variation analysis (MANOVA). These approaches allowed us to gain a deeper understanding of the evolutionary relationships and differences between the populations or species studied, contributing to an integrated and robust analysis of the biological data. Our results indicate the existence of a new taxon for Bothrops aff. atrox. Although phylogenetically closely related to B. atrox and sharing morphological characters with other specimens of the taxonomic group, it represents a cryptic species endemic to an upland Brejo in Ceará.